Tingkat keberhasilan hidup teripang gamat lumpur, Stichopus hermanni, hasil dari transverse fission - Tatalede, Putri A.; Salindeho, Indra R.N. (e-Journal BUDIDAYA PERAIRAN, 2018)
The aim of the experiment was to find out the survival rate of the sea cucumber (Stichopus hermanni) seeds generated from transverse-fission method, and cultured in the waters of Talengen gulf, Sangihe Islands Region.  Twenty five specimens of sea cucumber were collected around the waters of Talengen gulf and Pananuareng bay, the Region of Sangihe Islands.  The specimens were transported by boat to the field-research area of Nusa Utara Polytechnic, as the site of the experiment.  The specimens were kept individually in 25 plastic mesh cages, where each cage measured 40cmx40cmx40cm.    The individual body length of the specimens was measured  and then  was transversely  cut at the middle of the body antero-posteriorly.  The procedure was conducted underwater to prevent  expelling of the visceral organs.  25 individuals were applied transverse-fission,  hence 50 new individuals were generated, which were composed of 25 Anterior individuals (A) and 25 Posterior-individuals (P).   After transverse fission,  the Anterior- individuals (A) and Posterior-individuals (P), generated from the same individual were put back to their previous cage.  The new individuals were cautiously controlled, and at the interval of 6 hours observation on the sealing process of the open wound and the regenerating process were carried out. The result showed that the survival rate of the sea cucumbers generated from transverse-fission method, was as high as 70.83%.  The Posterior-individuals (P) had higher survival rate (75.66%) than Anterior-individuals (66%).   The result also showed that A and P individuals generated from larger individuals had lower survival rate than those from smaller individuals.   Small individuals sizing 6-14cm had highest survival rate, which was 100%, while larger individuals sizing 14-22cm and 22-30cm had lower survival rate which were 85.5%  and  27% respectively.     The sealing of the open wounded took averagely 4 days, while the process of the regeneration took around 4 weeks. Keywords: sea-cucumber, fission, survival-rate